Key concepts in media and communications - Jones, Paul; Holmes, David (Thousand Oaks, Calif. ; London : SAGE, 2011)
An approachable yet critical introduction to the basics of media and communication studies from two experts in the field.
Includes bibliographical references and index.
MC
Keywords: Communication; Mass media